2009
DOI: 10.1111/j.1467-9841.2008.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Translation style and participant roles in court interpreting1

Abstract: This paper investigates the translation styles of court interpreters in New York City and the styles' social and pragmatic implications for multilingual interactions in court. Interpreters are found to vary between using first or third person to represent the voice of a translated source speaker, thereby varying between adherence to explicit institutional norms that require first person and accommodation to non-professional interpreting practices that favor the use of reported speech. In a quantitative and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 28 publications
3
39
0
2
Order By: Relevance
“…In actual practice, studies have shown that interpreters, both professional and novice, often deviate from the direct speech convention (Angermeyer 2009;Bot 2005;Cheung 2012;Dubslaff & Martinsen 2005;Johnen & Meyer 2007;Takimoto & Koshiba 2009;van de Mieroop 2012). It has even been argued that interpreter neutrality suffers less when reported speech is used, since the use of direct speech implies that the interpreter identifies more closely with what is being said (Wallmach 2002).…”
Section: Direct Speech Vs Reported Speechmentioning
confidence: 94%
See 4 more Smart Citations
“…In actual practice, studies have shown that interpreters, both professional and novice, often deviate from the direct speech convention (Angermeyer 2009;Bot 2005;Cheung 2012;Dubslaff & Martinsen 2005;Johnen & Meyer 2007;Takimoto & Koshiba 2009;van de Mieroop 2012). It has even been argued that interpreter neutrality suffers less when reported speech is used, since the use of direct speech implies that the interpreter identifies more closely with what is being said (Wallmach 2002).…”
Section: Direct Speech Vs Reported Speechmentioning
confidence: 94%
“…In these cases, reported speech can help the listener to distinguish among multiple speakers, thus clarifying who is responsible for each utterance (Cheung 2012). Because reported speech makes the attribution of the interpreted utterance explicit, it can be particularly useful in helping lay participants, witnesses and defendants participate more actively in the court proceedings (Angermeyer 2009). …”
Section: Direct Speech In Court Interpretingmentioning
confidence: 96%
See 3 more Smart Citations